2017
DOI: 10.1002/lt.24781
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transplant accessibility for sensitized patients by avoiding unacceptable antigens

Abstract: Recent data have confirmed the negative impact of preformed donor-specific antibodies (pDSAs) after liver transplantation (LT). In order to reduce the risk of developing lesions associated with acute and chronic antibody-mediated rejection in LT recipients, we evaluated the consequences in terms of transplant accessibility, associated with avoiding pDSAs according to several mean fluorescence intensity (MFI) titer thresholds that have been previously reported to be relevant in LT. Among the 484 included LT can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…This observation was even more evident in LT recipients with preformed DSA (65.3% women). The result is in accordance with the published data [ 13 , 15 , 32 ] and explained by previous pregnancies as the main trigger for anti-HLA antibodies prior to solid organ transplantation [ 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…This observation was even more evident in LT recipients with preformed DSA (65.3% women). The result is in accordance with the published data [ 13 , 15 , 32 ] and explained by previous pregnancies as the main trigger for anti-HLA antibodies prior to solid organ transplantation [ 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…The lack of difference in the mortality rates between patients with and without pDSAs in our study confirms that considering accepted or unacceptable HLA antigens for LT is not required. We had previously reported that applying such an allocation strategy would dramatically reduce the accessibility to transplantation for a large proportion of patients …”
Section: Discussionmentioning
confidence: 99%
“…LT with pDSAs is a common situation because pretransplant sensitizing events (including blood transfusions) are frequent in patients on the waiting list and because the supposed weak detrimental effect of antibody‐mediated immunity leads transplant physicians to not consider the presence of pDSAs with graft acceptance . However, few data concerning the medium‐term and longterm impact of pDSAs exist.…”
mentioning
confidence: 99%
“…Thirty patients underwent LDLT, while 10 received deceased-donor LT. Preoperative recipient status was at-home (18), hospitalized (20), and intensive care unit-bound (2). The median MELD score was 20 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Sum-MFI of HLA Class-I, -II, and -I + II were 1643 (0-6909), 3871 (0-12,116), and 7124 (3904-17,995), respectively.…”
Section: Patient Characteristics In Pdsa-ltmentioning
confidence: 99%
“…The median age was 55 years (IQR: 43-59). Primary diseases included HCV (28), HBV (19), and primary biliary cholangitis (PBC) (17). Thirty patients were diagnosed with HCC.…”
Section: Patient Characteristics In Aboi-ldltmentioning
confidence: 99%